2017
DOI: 10.1038/onc.2017.132
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-secreted anterior gradient-2 binds to VEGF and FGF2 and enhances their activities by promoting their homodimerization

Abstract: The importance of the tumor microenvironment in targeted anticancer therapies has been well recognized. Various protein factors participate in the cross-talk between tumor cells and non-malignant cells. Anterior gradient-2 (AGR2) is overexpressed in diverse human adenocarcinomas and it exists in both intracellular and extracellular spaces. Although intracellular AGR2 has been intensively investigated, the function of secreted AGR2, especially its exact mechanism of action is still poorly understood. Here we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
54
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 48 publications
2
54
0
Order By: Relevance
“…Recent publication revealed that secreted AGR2 promotes endothelial cells and Fibro. migration to form tumor microenvironment [14]. This lead us to hypothesize that the possible role of AGR2 in wound-healing process is to promote the migration of various cell types for the wound-healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Recent publication revealed that secreted AGR2 promotes endothelial cells and Fibro. migration to form tumor microenvironment [14]. This lead us to hypothesize that the possible role of AGR2 in wound-healing process is to promote the migration of various cell types for the wound-healing process.…”
Section: Discussionmentioning
confidence: 99%
“…eAGR2 interacts with Vascular endothelial growth factor A via its thioredoxin motif. Furthermore, eAGR2 has been shown to directly bind to VEGF and fibroblast growth factor 2, which are the major players in tumour angiogenesis, and enhances their activities [Guo et al., ]. This enhancement is dependent on both the AGR2 self‐dimerisation region and the two signalling pathways.…”
Section: Agr2 and The Tnsmentioning
confidence: 99%
“…12,15 Another chaperon-like enhancer molecule anterior gradient-2 secreted from tumor cells has been shown to activate VEGF and fibroblast growth factor and suggested as a potential therapeutic target. 41 Other than exosomal miRNAs, secreted cytokines and extracellular peptides, tumor secreted metabolites have been seen as a new class of therapeutic targets and tumor biomarkers. 26,97,102,108 For an example, Salimian Rizi et al 102 reported that use of inhibitor of arginine, secreted metabolite in TME can serve as therapeutic by dismantling the metabolic crosstalk between developmental adipose stromal cells and endometrial and ovarian tumor cells.…”
Section: Therapeutic Approaches To Modulate Tmementioning
confidence: 99%